Lesson planning for high school physical education meeting the national standards & grade-level outcomes - MacDonald, Lynn Couturier 1959-; Doan, Robert John; Chepko, Stevie (Human kinectics, 2018)
"Provides standards-based, ready-to-use lesson plans that enhance student learning and help students become physically literate individuals. This book also provides guidance on how to plan effective lessons that align with SHAPE America's National Standards and Grade-Level Outcomes for K-12 Physical Education. Lesson Planning for High School Physical Education is written by master teachers and edited by SHAPE America. In this book, you'll find: more than 240 sequential and comprehensive lesson plans that provide aggressive practice tasks that integrate assessments to evaluate and monitor student progress; innovative and unique modules on topics such as fly fishing, rock climbing, line dance, yoga, and more, as well as more traditional modules; an introductory chapter that presents the key points for the grade span, providing teachers and PE majors and minors a clear roadmap for planning curricula, units, and lessons; lessons that reflect best practices in instruction, helping teachers enhance their effectiveness; [and] expert guidance in delivering quality lessons that are designed to reach objectives and produce outcomes, and not just keep student occupied"-- Provided by publisher.